A history of early stent thrombosis is associated with prolonged clot lysis time - Pankiw-Bembenek, Oksana; Zalewski, Jaroslaw; Goralczyk, Tadeusz; Undas, Anetta (Thrombosis and Haemostasis, 2012)
It has been demonstrated that formation of compact plasma fibrin clots resistant to plasmin-mediated lysis characterises patients following instent thrombosis (IST). The relationship between defective fibrinolysis, reflected as prolonged clot lysis time (CLT) and IST is unclear. We sought to investigate whether patients with acute and subacute IST have impaired fibrinolytic capacity. We studied 41 definite IST patients, including 15 with acute and 26 with subacute IST experienced 2–73 months prior to enrollment, versus 41 controls matched for demographics, cardiovascular risk factors, concomitant treatment and angiographic/stent parameters. CLT, reflecting lysis of a tissue factor-induced plasma clot by exogenous tissue plasminogen activator, together with plasminogen activator inhibitor-1 (PAI-1) antigen and activity, thrombin-activatable fibrinolysis inhibitor (TAFI) antigen and activity, thrombomodulin (TM), plasminogen and α2-antiplasmin (α2AP) were measured. There were no inter-group differences in angiographic parameters, indication to the first PCI, culprit vessel or a type of stent. Patients with IST had 11% longer CLT (p=0.005) and 13% higher PAI-1 antigen (p=0.04) compared to controls. There were positive correlations in both groups between CLT and PAI-1 antigen and TAFI activity (all p<0.001). Multiple regression analysis showed that CLT (odds ratio [OR]=1.04 per 1 minute, 95% CI 1.01–1.08, p=0.02) and platelet count (OR=1.01 per 1,000/μl, 95% CI 1.00–1.02, p=0.034) were independent predictors of IST (R2=0.28, p<0.05). Concluding, impaired fibrinolytic potential, that is in part determined by plasma PAI-1 antigen and TAFI activity, characterises patients with a history of acute and subacute IST, which might help identify patients at higher risk of IST.
Keywords: Thrombosis; clot lysis time; hypofibrinolysis; stents